Skandinaviske studier og geopolitik: IASS og den kolde krig - Jelsbak, Torben (Scandinavistica Vilnensis, 2023)
The foundation stone for the creation of IASS was laid at the First International Conference on Scandinavian Studies which took place at the University of Cambridge, England, in July 1956. Few months later, the world woke up to the news of the Soviet invasion in Budapest on November 4th, a defining moment in the history of the Cold War, which sent political shock waves and a flow of nearly a quarter-million Hungarian refugees to Western Europe. But how did this tense political situation affect the emerging field of international Scandinavian studies? Drawing on the vast literature of published proceedings from IASS conferences and personal interviews with members of the organization, this article examines how the Cold War geopolitical conflict between the communist East and the capitalist West left its imprint on the activities of IASS in the period from 1956 until the Fall of the Berlin Wall and the dissolution of the Soviet Union in 1989/1991.